An investigation of the psychological stress of medical staff in Shanghai shelter hospital during COVID-19 - Zhou, Yaqing; Liu, Aiming; Pu, Zunguo; Zhou, Minlu; Ding, Hongsheng; Zhou, Jia (Frontiers in Psychology, 2023)
motivation: The purpose of this study is to understand the psychological status of medical workers under the new coronavirus pneumonia epidemic, and to provide a basis for psychological crisis intervention plans under designated emergencies. Method:The questionnaires were used to investigate the general information questionnaire, health questionnaire depression scale, generalized anxiety scale, insomnia severity index scale and mental health self-assessment questionnaire.Results:There were no statistically significant differences in the incidence rates of anxiety, depression, and sleep disorders among subjects of different genders, ages, and educational levels.There were statistically significant differences in the incidences of anxiety, depression, stress response and sleep disturbance among subjects with different levels of worry about the COVID-19 (P<0.05).Conclusion: During the outbreak of the COVID-19, we should do a good job in the relevant business and psychological training of medical workers to enhance their psychological resilience.It is suggested that medical institutions should pay attention to the mental health of medical workers, strengthen psychological counseling and humanistic care, and reduce stress.